EFFECT OF THE ADDITIONOF BEETROOT(Beta vulgaris L) AS NATURAL COLOURING ON THE QUALITY OF SMALL SHRIMP (Acetes erythraeus)PASTE - Julian Suhrawardi; Suparmi Suparmi; Dewita Buchari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was intended to find out the effect of the addition ofbeetroot (Beta vulgaris L) on the quality of small shrimp (Acetes erythraueus) paste. The design used was Completely Randomized Design (CRD) non factorial, with addition of different concentration of beetroot which consists of four levels i.e. without addition Beetroot (B), 5% beetrot (B), 10% beetrot (B), and 15% beetrot (B) with three replicated, so there were 12 experimental units. The tested parameters were organoleptic and chemical analysis, for organoleptic includes appearance, aroma and texture, and for chemical analysis includes water, ashcontent, and Non Protein Nitrogen (NPN). The result of the research showed that the treatment with 5% addition of beetroot was the best treatment for organoleptic and chemical analysis, with appearance, aroma, and texture; water, ash content  and NPN were 5.00, 3.19, 5.59; 7.77%, 2.90% and 0.37%, respectively.Keywords : Beetroot, Natural colouring, Shrimp Paste, Small shrimp